(untitled) (Journal of actual problems of jurisprudence, 2016)
For any question about the state of national security will always be relevant, to the dictates it will become more complicated and unite themselves in all aspects of government and public and turned into a well-organized political tool. With the increasing globalization issue of national security and especially the direction of economic security it took a very important place. In order to participate in the affairs of the world community as a full-fledged independent state need economic power, and it is a measure of the state. Create and implement solutions to ensure the national economy of the Republic of Kazakhstan depends on the structure and functioning of government. Most importantly, in ensuring economic security, they should be responsible for regulating the execution of long-term and short-term obligations for the repetition of the distribution of responsibilities and specific liability companies and functions.